2020
DOI: 10.1016/j.carbon.2019.09.070
|View full text |Cite
|
Sign up to set email alerts
|

Understanding cooperative loading in carbon nanotube fibres through in-situ structural studies during stretching

Abstract: Carbon nanotube (CNT) fibres are firmly established as a new high-performance fibre, but their tensile mechanical properties remain a relatively small fraction of those of the constituent CNTs. Clear structure-property relations and accurate mechanical models are pressing requirements to bridge this gap. In this work we analyse the structural evolution and molecular stress transfer in CNT fibres by performing in-situ synchrotron wide-and small-angle X-ray scattering and Raman spectroscopy during tensile deform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…These results confirm that bulk properties of the CNT fibres are dominated by inter-particle rather than intraparticle features, and that degree of CNT perfection, for example as given by the intensity of D/G ratios, is not an adequate predictor of tensile properties. CNT fibres are fibrillary solid with mechanical failure through pull out of CNTs and no evidence of CNT fracture [6,22,23]; hence, the defect density of constituent CNTs does not directly limit tensile strength. We also note the significant increase in all longitudinal properties for higher synthesis temperatures and when using toluene instead of butanol as a carbon source.…”
Section: Effect Of Composition On Mechanical Properties Of Cnt Fibresmentioning
confidence: 99%
“…These results confirm that bulk properties of the CNT fibres are dominated by inter-particle rather than intraparticle features, and that degree of CNT perfection, for example as given by the intensity of D/G ratios, is not an adequate predictor of tensile properties. CNT fibres are fibrillary solid with mechanical failure through pull out of CNTs and no evidence of CNT fracture [6,22,23]; hence, the defect density of constituent CNTs does not directly limit tensile strength. We also note the significant increase in all longitudinal properties for higher synthesis temperatures and when using toluene instead of butanol as a carbon source.…”
Section: Effect Of Composition On Mechanical Properties Of Cnt Fibresmentioning
confidence: 99%
“…More studies evaluated the inuence of hybrid reinforcement, such as a combination of carbon ber (CF) and carbon black with CNTs on the self-sensing properties of cement-based sensors. 25,40,72,[78][79][80][81] Anthony et al 80 developed computational models of a composite for predicting the benets of graing CNTs at the CF surface in order to create a conductive network that can be used for in situ damage detection. Moreover, Han et al 81 showed that the exural strength and electrical conductivity in the cement mortar matrix with self-assembled CNT/nano carbon black composite llers are enhanced and stable, and sensitive piezoresistivity is achieved at a low ller content.…”
Section: Inuence Of Conductive Laments On Concretementioning
confidence: 99%
“…The conguration of CNTs to aligned bers is recognized as a natural embodiment for a one-dimensional material and the most effective to transfer axial properties to the macroscale. 54,78 Carbon nanotube networks are highly valuable in SHM for strain mapping, damage detection and identication of crack initiation and propagation. 54 Abot et al 92 produced a thread spun from carbon nanotube forests by growing and drawning CNT forests that were twisted into a ne thread (or yarn) in order to be used as the sensor element.…”
Section: Smart Materialsmentioning
confidence: 99%
“…In order to realize the creation of the shish-kebab crystalline structures in the PLA/PPDO blend system, it is first necessary to make PPDO uniformly dispersed in the PLA matrix. Then, taking advantage of the strong shear force field during processing, the PPDO dispersed phases could be in situ fibrillated along the flow direction to form the highly oriented fibrillar structure [ 6 , 25 ] which could possibly act as shish during crystallization and then be advantageous to the shish-kebab crystallization formation. As we know, extrusion and injection molding are the two well-known polymer processing techniques featured with shear force field.…”
Section: Introductionmentioning
confidence: 99%